AUTOMATED STUDENT ACCOMMODATION BOOKING SYSTEM - CHOY, SHAO KEAT (IRC, 2020)
The name of this project is Automated Student Accommodation Booking System which is proposed by Mr. Choy Shao Keat. The main purpose of this project is to develop a web-based system that can resolve current accommodation registration issues that are facing by UTP students. Besides, it also aims to automate the manually done task to reduce UTP Residential Village Management Team’s workload. Evolution of technology has allowed digitalization of manually done activities onto digital platform, thus save time and resources. In the past few years, many universities have started to digitalize their student accommodation booking activities by implementing online booking system. Hence, the literature review presents studies that have been conducted in this area and similar systems that are available in other universities. These studies allow the author to brainstorm ideas as well as enhancing the features that are already available on these systems. Furthermore, the methodology that has been chosen for this the development of this system is Agile methodology. The reasons for choosing this methodology is to achieve higher product quality and reduce risk of project failure. Scrum meetings and sprint review in Agile methodology also provides a better visibility into project performance. Despite that, this report aims to clarify and emphasize the importance of the development of this project and how relevant it is to the UTP Students Community as well as UTP Residential Village Management Team. The system design is based on the existing accommodation booking system. Besides that, the room booking concept that is available in hotel booking system will be a reference to the proposed system. The proposed system aims to provide a set of useful features to both students and Residential Village Management Team, at the same time providing high level of user friendliness to all users. Last but not least, the conclusion and future work will describe how this project can sustain as well as explaining future development process that is going to be done by the author.